Perfect symbol recovery and NBI suppression in MIMO‐OFDM systems. Issue 3 (1st January 2014) - Darsena, D.; Gelli, G.; Verde, F.
Abstract : It is shown that by exploiting the degrees of freedom arising from the use of multiple antennas and/or insertion of virtual carriers in multiple‐input multiple‐output (MIMO) orthogonal frequency‐division multiplexing (OFDM) systems, perfect symbol recovery and complete narrowband interference (NBI) cancellation can be achieved in the absence of noise by means of constrained minimum mean‐output‐energy linear filtering. Moreover, a nonlinear iterative scheme is proposed to improve NBI rejection in realistic operative conditions.